The subject was roses [videorecording (DVD)] - Grosbard, Ulu; Neal, Patricia, 1926-2010; Albertson, Jack, 1910-1981; Sheen, Martin; Gilroy, Frank D. (Frank Daniel), 1925-2015 (Distributed by Warner Home Video, 2009)
A lovely gesture - a bouquet of roses - from husband to wife becomes the catalyst for a clash of long-repressed emotion. Their son has just come back from war, but is caught in the middle of their conflict.